Functionalized magnetic nanomaterials in agricultural applications - Spanos, Alexandros; Athanasiou, Kyriakos; Ioannou, Andreas; Fotopoulos, Vasileios; Krasia-Christoforou, Theodora (My University, 2021)
The development of functional nanomaterials exhibiting cost-effectiveness, biocompatibil-ity and biodegradability in the form of nanoadditives, nanofertilizers, nanosensors, nanopesticides and herbicides, etc., has attracted considerable attention in the field of agriculture. Such nanoma-terials have demonstrated the ability to increase crop production, enable the efficient and targeted delivery of agrochemicals and nutrients, enhance plant resistance to various stress factors and act as nanosensors for the detection of various pollutants, plant diseases and insufficient plant nutri-tion. Among others, functional magnetic nanomaterials based on iron, iron oxide, cobalt, cobalt and nickel ferrite nanoparticles, etc., are currently being investigated in agricultural applications due to their unique and tunable magnetic properties, the existing versatility with regard to their (bio)functionalization, and in some cases, their inherent ability to increase crop yield. This review article provides an up-to-date appraisal of functionalized magnetic nanomaterials being explored in the agricultural sector.
Keywords: Agriculture; Functionalized magnetic nanomaterials